Penerapan Supervisi Akademik Dengan Teknik Individual Dalam Meningkatkan Kedisiplinan Mengajar Guru - Jasmin (Education Reserach Center, 2025)
This study aims to improve teachers' teaching discipline through the implementation of academic supervision using an individual technique at SDN Komplek Kenjeran II-506 Surabaya. This individual coaching technique is applied because the issues faced by teachers related to discipline and performance vary greatly, necessitating a personal and specific approach. The method used in this study is School Action Research (SAR), which involves collaboration between the principal and teachers in designing, implementing, and evaluating improvement actions. The results of the study show that academic supervision using individual techniques significantly improves teachers' discipline and performance in preparing Lesson Plans (RPP). This improvement is reflected in the positive changes in the quality of learning documents as well as the implementation of classroom learning. Thus, this supervision technique is effective in addressing the problems of teachers' discipline and performance at SDN Komplek Kenjeran II-506 Surabaya and can be used as a sustainable coaching strategy to enhance the quality of education.